Wind buckling of metal tanks during their construction - Jaca, Rossana Claudia (2010)
Shell structures are usually designed by considering their final shape and configuration, so that it is assumed that stability during the construction will be satisfied without further thought. However, evidence from recent collapses of metal tanks under moderate winds shows that this is a matter that requires special attention. This paper reports analytical studies of tanks for the oil industry that failed during their construction in the Argentinean Patagonia under moderate winds. The cylindrical part of the tanks was set up in place with point welding, but the roof was not yet in place at the time of collapse. To understand the mechanism of failure, static, geometrically nonlinear finite element modeling of the tanks was carried out, in which the shell was represented as close as possible to the actual conditions during the construction stage at which it failed. The results show that for the wind velocities prevalent at the time of collapse, an explanation of the failure mechanism can only be achieved by taking into account several special features of the structure under construction, i.e. the localized nature of welding and the influence of the incomplete junction with the bottom plate.